Second Five Year Plan: Administration and Organisation - Planning Commission, Government of India (Planning Commission, Government of India, 1956)
At the present time the general, social and economic outlook which has been evolved in India in dealing with problems of national development embodies a large measure of agreement both on the analysis of problems and on many of the basic questions of policy. On closer examination, differences in judgement are often found to be either differences in perspective or differences in detail. While the area of agreement on matters of policy is considerable, doubt exists whether in its range and quality administrative action will prove equal to the responsibilities assumed by the Central and State Governments in the second five year plan. It is likely that as the plan proceeds difficult issues will relate less to matters of policy and approach.
Planning Commission Government of India
Planning Commission Government of India
Keywords: Administration and Organisation; Personnel Requirements and Training Programmes